Romanticism, race, and imperial culture, 1780-1834 - Richardson, Alan, 1955-; Hofkosh, Sonia (Indiana University Press, 1996)
These 13 original essays re-examine a wide selection of romantic-era writers, texts, and genres to explore the relation between romanticism as a literary field and the emergence of the second British empire during the formative period 1780-1834. Extending feminist and historicist inquiry with the insights of postcolonial critique, these essays rethink some of the pivotal concepts that have informed romantic studies, from the largely unanalyzed construction of race as a category of European political and literary culture to how the notion of the solitary imagination functions in capitalism's imperialist enterprise.